Advanced Cisco Routing: RIP and EIGRP. - Rivera, Jarrel (linkedin.com, 2022)
Explore topics and techniques in Cisco routing, from basic concepts and RIP configuration to advanced dynamic routing for enterprise networks with EIGRP.